Recent developments in capabilities for analysing chlorinated paraffins in environmental matrices: A review. (October 2015) - van Mourik, Louise M.; Leonards, Pim E.G.; Gaus, Caroline; de Boer, Jacob
Highlights: The current state of CP determination was evaluated. Methods for the determination of CPs need further harmonization and validation. New methods such as based on TOF-MS are becoming available. Analytical standards for individual congeners and certified reference materials are not available yet. International interlaboratory studies are ongoing and show some progress. Abstract: Concerns about the high production volumes, persistency, bioaccumulation potential and toxicity of chlorinated paraffin (CP) mixtures, especially short-chain CPs (SCCPs), are rising. However, information on their levels and fate in the environment is still insufficient, impeding international classifications and regulations. This knowledge gap is mainly due to the difficulties that arise with CP analysis, in particular the chromatographic separation within CPs and between CPs and other compounds. No fully validated routine analytical method is available yet and only semi-quantitative analysis is possible, although the number of studies reporting new and improved methods have rapidly increased since 2010. Better cleanup procedures that remove interfering compounds, and new instrumental techniques, which distinguish between medium-chain CPs (MCCPs) and SCCPs, have been developed. While gas chromatography coupled to an electron capture negative ionisation mass spectrometry (GC/ECNI-MS) remains the most commonly applied technique, novel and promising use of high resolution time of flight MS (TOF-MS) has also been reported. We expect that recent developments in high resolution TOF-MS and Orbitrap technologies will further improve the detection of CPs, including long-chain CPs (LCCPs), and the group separation and quantification of CP homologues. Also, new CP quantification methods have emerged, including the use of mathematical algorithms, multiple linear regression and principal component analysis. These quantification advancements are also reflected in considerably improved interlaboratory agreements since 2010. Analysis of lower chlorinated paraffins (5 ) remains, however, challenging and better approaches to analysing these homologues are needed. Furthermore, suitable quantification standards would facilitate improving the quality of CP analysis.